Critical properties, heat capacities, and thermal diffusivities of four saturated triglycerides. (October 2017) - Bogatishcheva, Nataliya S.; Faizullin, Mars Z.; Popov, Alexander P.; Nikitin, Eugene D.
Highlights: Critical properties, heat capacities, thermal diffusivities of four triglycerides were measured. The triglycerides studied have 8, 10, 12, 14 carbon atoms in a parent acid. The triglycerides decompose at near-critical temperatures. Pulse-heating method with short residence times was used. Abstract: The critical temperatures, pressures, heat capacities, and thermal diffusivities of saturated triglycerides C3 H5 [Cn H2n-1 O2 ]3 with n = 8, 10, 12, 14 have been measured. The experimental critical constants of triglycerides have been compared with those calculated using the group contribution methods of Constantinou and Gani, Marrero and Gani, Hukkerikar and co-workers, and Cunico and co-workers. The heat capacities and thermal diffusivities have been measured in the temperature range from about the melting point of a triglyceride to 410–425 K. The temperature dependencies of the heat capacities and thermal diffusivities have been approximated by a third-order and a first-order polynomial, respectively. The coefficients of these polynomials have been given. Using the experimental data, the thermal conductivities of triglycerides have been calculated.